2009
DOI: 10.1002/aic.12104
|View full text |Cite
|
Sign up to set email alerts
|

High throughput synthesis and screening of new protein resistant surfaces for membrane filtration

Abstract: A novel high throughput method for synthesis and screening of customized proteinresistant surfaces was developed. This method is an inexpensive, fast, reproducible and scalable approach to synthesize and screen protein-resistance surfaces appropriate for a specific feed. The method is illustrated here by combining a high throughput platform (HTP) approach together with our patented photo-induced graft polymerization Additional Supporting Information may be found in the online version of this article.Correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
66
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 71 publications
7
66
0
5
Order By: Relevance
“…18,20 The thickness of the PES layer (before grafting) was 159 ± 31 nm in water and 45 ± 17 nm in isobutanol. The thickness after grafting was 208 ± 44 nm in water, but could not be measured accurately in isobutanol (Supporting Information Figure S4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…18,20 The thickness of the PES layer (before grafting) was 159 ± 31 nm in water and 45 ± 17 nm in isobutanol. The thickness after grafting was 208 ± 44 nm in water, but could not be measured accurately in isobutanol (Supporting Information Figure S4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The magnitude of resistance was generally greater after protein solution filtration as compared with static adsorption, because resistance was developed by different mechanisms (e.g., during filtration, permeation drag causes mass accumulation on the membrane surface and in the mem- brane pores and may induce protein aggregation); still, the two approaches exhibited similar trends in measured resistance. Zhou et al [1][2][3] have identified several promising monomers with the high throughput platform. These monomers were tested in benchscale filtration experiments with mixing to assess the scalability of the results and whether surfaces that exhibited low protein interactions after adsorption would also be favorable for filtration applications.…”
Section: Discussionmentioning
confidence: 99%
“…What we urgently need is a fast, efficient and reproducible process to allow for quick selection of the best polymer, and subsequent analysis of its mechanism to find "rules" for future design of surfaces for membrane and other separations. We have recently developed and reported such a method in the literature, by adapting a high throughput platform (HTP) to the facile modification of commercial PES membranes, using HTP together with photo-induced graft polymerization (PGP) [1][2][3]. We call this method HTP-PGP.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations